Availability and utilization of skilled attendants for child birth: implications for maternal and human resources development in Nigeria (2015)
Shortage of manpower has been a major concern in health care delivery system. Poor utilization of skilled attendants for childbirth has been linked with high maternal mortality in developing nations. The effect has been quite deleterious and has contributed to the shortfalls in the achievement of set health goals. This shortage heavily influences the effective and efficient delivery of services especially in rural communities in Nigeria. Preventable complications of childbirth have resulted in the death of many women during the process of bringing life. The countries that have identified and addressed the issue of skilled attendance at childbirth have witnessed a tremendous reduction in Maternal Mortality. This paper presents a review of availability and utilization of skilled attendants for child birth: Implications for Maternal Mortality and human resources development in Nigeria. It is aimed at highlighting the need for more attention in improving Human resources for maternal and child health care. Anderson’s model of Health care utilization was used to illustrate Health care utilization. Publications on skilled birth attendants, maternal mortality, human resources for health were also reviewed. This review identified that Nigeria is among the countries with shortage in human resources for health and utilization of skilled attendants was below expectation, with slow decline in maternal mortality. Therefore, there is need for more political will in ensuring that the resources needed to improve health care receive more investment. More effort should be made to improve infrastructures in the rural communities to enhance staff retention and access to care.